An Investigation on the Growth and Characterization of Thiourea Single Crystal Grown from Aqueous Solutions (Journal of Bangladesh Academy of Sciences, 2009)
Thiourea single crystals have been grown from aqueous solution by slow cooling technique. The stability of the saturated solutions of different pH values has been assessed by measuring the metastable zone width (MSZW) by a nucleation method. MSZW has been enhanced by the influence of pH of thiourea solution. The growth rate of the thiourea crystal along the c-direction [001] was found faster for the higher pH value of the solution. The structural, optical and mechanical properties of the grown crystals were characterized by FT-IR spectroscopy, UV-Vis spectroscopy and powder X-ray diffraction. FT-IR and UV-Vis spectra provide information about the presence of functional groups. The Vicker's micro-hardness study has been performed on the grown crystals and the results reveal the softening nature according to Onistch concept. The growth features of the thiourea crystals were observed by etching study. A hexagonal spiral growth was observed on the [001] faces of thiourea crystals.  DOI: 10.3329/jbas.v33i1.2951 Journal of Bangladesh Academy of Sciences, Vol. 33, No. 1, 63-70, 2009